Pilot-scale co-processing of lignocellulosic biomass, algae, shellfish waste via thermochemical approach: Recent progress and future directions. (March 2022) - Yek, Peter Nai Yuh; Wan Mahari, Wan Adibah; Kong, Sieng Huat; Foong, Shin Ying; Peng, Wanxi; Ting, Hiram; Liew, Rock Keey; Xia, Changlei; Sonne, Christian; Tabatabaei, Meisam; Almomani, Fares; Aghbashlo, Mortaza; et al.
Graphical abstract: Highlights: Review on thermal co-processing of lignocellulosic biomass, algae, shellfish waste. Design, operation, key parameters of pilot-scale reactors are discussed. Techno-economic analysis and synergistic effects of co-processing are discussed. Co-pyrolysis allows high energy recovery, co-gasification shows high profitability. Carbon credit makes thermal co-processing more sustainable to utilise biomass. Abstract: Thermal co-processing of lignocellulosic and aquatic biomass, such as algae and shellfish waste, has shown synergistic effects in producing value-added energy products with higher process efficiency than the traditional method, highlighting the importance of scaling up to pilot-scale operations. This article discusses the design and operation of pilot-scale reactors for torrefaction, pyrolysis, and gasification, as well as the key parameters of co-processing biomass into targeted and improved quality products for use as fuel, agricultural application, and environmental remediation. Techno-economic analysis reveals that end product selling price, market dynamics, government policies, and biomass cost are crucial factors influencing the sustainability of thermal co-processing as a feasible approach to utilize the biomass. Because of its simplicity, pyrolysis allows greater energy recovery, while gasification has the highest net present value (profitability). Integration of liquefaction, hydrothermal, and fermentation pre-treatment technology has the potential to increase energy efficiency while reducing process residues.